Terbutaline and Associated Risks for Neurodevelopmental Disorders. (15th July 2014) - Perna, Robert; Loughan, Ashlee; Perkey, Hana; Tyson, Kelly
Abstract : Preterm labor often leads to a preterm birth and has been shown to be the most important determinant of risk for perinatal morbidity and mortality. While medication management has been utilized by physicians to delay preterm labor, the results these medications achieve remain inconsistent, in addition to increasing the risk to the developing fetus. Terbutaline has been among the most commonly usedβ 2 -adrenoreceptor (β 2 AR) agonists in the management of preterm labor. The research suggests that tocolytic terbutaline therapy carries a significant risk for the mother and the child, which can be magnified by extended exposure, sex of the fetus, and administration during critical fetal developmental periods. This paper highlights the research on terbutaline in treatment of preterm labor, along with the possible associated cognitive deficits in adolescents who were treated with terbutaline in utero. Two case summaries are presented to illustrate the potential deficits in clinical presentations of adolescents with history of intrauterine exposure to terbutaline. Publicizing the association between terbutaline and these deficits can not only assist obstetricians and expectant mothers in making a more informed choice in the treatment of preterm labor but also provide neuropsychologists and pediatricians with information helpful in understanding the etiology of these impairments.